Evaluating cobalt-based hydroxide nanosheets with mesopores as an enhanced electrocatalyst for the oxygen evolution reaction - Ng, Matthew Jun Ye (2019)
The demand for clean energy has motivated people to look for fuel alternatives and hydrogen fuel was found to have zero carbon emissions while contributing to high current densities. However, pure hydrogen is hard to obtain from the atmosphere due to its light weight and water splitting technologies are being relied upon. Water splitting consists of a hydrogen evolution reaction (HER) and an oxygen evolution reaction (OER) where electrocatalysts are normally utilized to enhance their efficiency. Since the OER is known to suffer from the need for high overpotential and poor kinetics, electrocatalysts like Ru, Ir, and their oxides have been widely depended on. However, this surges the cost of producing hydrogen as Ru and Ir are considered to be very rare, hence, expensive. Past studies have produced various electrocatalysts with various morphologies and structures from different materials. However, their methods are considerably complex that may surface certain issues in a large-scale water splitting process. In an attempt to solve these issues(high cost of materials and complex synthesis methods), we have resorted in coming up with a simple yet suitable synthesis method from the use of Co as the base of OER electrocatalyst. To further enhance its catalytic performance, we incorporate it with a mesoporous structure and a nanosheet morphology. Physical characterization techniques like the secondary electron imaging (SEI), energy dispersive X-ray spectroscopy (EDX), and the X-ray Diffraction (XRD) were used to quality control the samples before proceeding to the electrochemical measurements. The electrochemical measurements consist of Linear Sweep Voltammetry (LSV), Tafel slope comparison, Time-dependent current density curve comparison, and the Nyquist plots comparison. These measurements serve to evaluate the viability of our sample as an efficient and stable OER electrocatalyst. All the results came out promising and as intended where our sample outperforms industrial benchmark like the RuO2. The results of the precursors were also compared against and it was shown that the mesoporous structure and the nanosheet morphology had a huge contribution to the success of our electrocatalyst. However, the objective of this project is only applicable an alkaline medium of the OER, hence, it is recommended that further studies be done for electrocatalysts in an acidic medium. Moreover, future studies should explore into various morphologies of our electrocatalyst that could potentially bring greater improvements.